2020
DOI: 10.1002/bse.2512
|View full text |Cite
|
Sign up to set email alerts
|

Exploring an innovative pivot: How green training can spur corporate sustainability performance

Abstract: In general, studies on green innovation practices have primarily taken an innovation view to study the costs and benefits to firms. What has been less examined, however, is how green training spurs the intentions and advantages of green innovation. Thus, this paper explores how and when green training influences the likelihood of firms to achieve sustainability performance by using organizational learning theory. Using a dataset of 231 Chinese manufacturing firms, our work shows that green training is positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 69 publications
4
48
0
Order By: Relevance
“…Although several manufacturing organisations across developed and emerging economies exhibit the potential to produce meaningful green innovations, such potential alone is no guarantee for investments by potential stakeholders (Abdu & Jibir, 2018; Dangelico et al, 2016; Melander, 2017). Given the rising global warming uncertainties and radical technological advancements, organisations consequently need to cultivate their LSC and strengthen their green creativity to bolster further green initiatives that provide evidence for investors (Jabbour, 2013; Xie & Zhu, 2020). However, several organisations that exhibit green creativity struggle to gain or sustain the competitive edge needed to drive their GOIE (Liao & Tsai, 2018; Song & Yu, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Although several manufacturing organisations across developed and emerging economies exhibit the potential to produce meaningful green innovations, such potential alone is no guarantee for investments by potential stakeholders (Abdu & Jibir, 2018; Dangelico et al, 2016; Melander, 2017). Given the rising global warming uncertainties and radical technological advancements, organisations consequently need to cultivate their LSC and strengthen their green creativity to bolster further green initiatives that provide evidence for investors (Jabbour, 2013; Xie & Zhu, 2020). However, several organisations that exhibit green creativity struggle to gain or sustain the competitive edge needed to drive their GOIE (Liao & Tsai, 2018; Song & Yu, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Firms should also be aware that implementing GTL style alone might not be sufficient for green employee engagement in order to spur environmental sustainability. As our findings suggest, green training should also be incorporated to provide employees with better knowledge on green practices (Cop, Alola, & Alola, 2020; Xie & Zhu, 2020). Therefore, our study highlights the benefits for business to be environmentally friendly.…”
Section: Discussionmentioning
confidence: 96%
“…It is suggested that green training enables the organization to achieve eco-friendly managers who indulge in environmentally friendly activities and promote sustainability [ 32 ]. It implies that the organizations should not only train their employees according to best business practices with green initiatives but should also encourage the customers to become more environmentally friendly and promote the practice of buying green products [ 33 ].…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%